Globalization: A Eucharistic Challenge (Hekima Review, 2005)
Globalization is an outstanding “sign of the time” in the world today.This phenomenon, which thrives on technological advancement andthe neo-liberal market system, is fast blurring national boundariesand dragging peoples into a complex network of inter-relationships andinterdependencies. But this has also created a sense of vulnerability (disease, terrorism,etc) and led to a lot of socio-economic injustice. With regards to the economicaspect of globalization, a remarkable economist, Joseph Stiglitz, notes that“globalization is a powerful force that has brought enormous benefits to some.Because of the way it has been mismanaged, however, millions have not enjoyedits benefits, and millions more have even been made worse off.